STUDENTS' ATTITUDE ANALYSIS TOWARD LEARNING MATHEMATICS - Fitri Wulan Sari; Nabil Maulana Yuspelto; Yusuf Devan Nr; Wahyu Lestari Utami; Siti Nurhalimah; Nana Karina Mayda; Dedek Andrian; Revika Nofriani (UIR PRESS, 2023)
This study has a goal, namely to describe the attitudes of junior high school students towards learning Mathematics. Disclosure of students' attitudes in learning mathematics is based on low mathematics learning outcomes at the junior high school level in Siak and Rokan Hulu Regencies, Riau Province. The type of research used is evaluation. The sample for this research was obtained from some students who were in Siak and Rokan Hulu Regencies, Riau Province. By using a sampling technique in the form of random sampling and data collection techniques in the form of surveys. The instrument used in this study was a questionnaire, to measure junior high school students' attitudes towards learning mathematics. Before the instrument was used, the instrument in the form of a questionnaire was validated in terms of content and construct. In terms of content, validity analysis used the aiken formula while construct validity used second order CFA. Statistical analysis by calculating the average and standard deviation and consulting the assessment guide table to obtain an assessment of individual student attitudes. The evaluation results show that the attitude of SMP towards learning mathematics is in the category of good students. Keywords: Attitude analysis, mathematics learning, junior high school